Professor PEI Ruixia’s Experience of Harmonizing in the Treatment of Diabetes Mellitus and Its Complications - Wu, Qiong; Pei, Ruixia (Journal of Contemporary Medical Practice, 2024)
Diabetes mellitus and its complications, as one of the current challenges in clinical treatment, treated by traditional Chinese medicine with the advantages of individualization and targeting. This paper elaborates on Prof. Pei Ruixia's experience in analyzing the etiology and treatment of diabetes mellitus and its complications based on theories of traditional Chinese medicine (TCM). Prof. Pei believes that abnormal liver function is the core cause of diabetes and its complications. The " Harmonizing " is advocated throughout the treatment. The overall treatment is based on the basic idea of "reconciling Shaoyang and harmonizing yin and yang", with calm medication and a comprehensive approach.